Birth of the Canadian Digestive Health Foundation - Ivan T Beck (Canadian Journal of Gastroenterology)
The Canadian Digestive Disease Foundation, renamed the Canadian Digestive Health Foundation -- Fondation canadienne pour la promotion de la santé digestive -- in December 2001, is the culmination of ongoing efforts by the Canadian Association of Gastroenterology to establish an independent charitable organization. In February 2001, it was officially endorsed as the Foundation for the Canadian Association of Gastroenterology. The initial efforts to establish this Foundation, led by Dr Richard McKenna in 1963, were unsuccessful. In 1991, Glaxo Canada (now GlaxoSmithKline) became a founding donor, and with the four founding physicians -- Drs Ivan T Beck, Richard H Hunt, Suzanne E Lemire and Alan BR Thomson -- the expenses to establish the Foundation were met. A charitable number was obtained in 1995 (0997427-11). The second founding donor was Janssen Canada (now Janssen-Ortho), and public education support came from Astra Canada (now AstraZeneca Canada). The Foundation initially relied on corporate donors, but now approaches physicians, patients and the general public. The objectives of the Foundation are to advance the science of gastroenterology and to provide knowledge of digestive diseases and nutrition to the general public, to enhance the quality of life of persons who are afflicted with these disorders. The major achievements of the Foundation are the provision of one-year operating grants to new investigators, which have allowed them to accumulate early data and subsequently obtain support from other major granting organizations. It also provides Fellowships and studentship support grants, in conjunction with the Canadian Institutes of Health Research and the pharmaceutical industry. The education committee found that there was little research support in this field, considering the large economic burden of digestive disease and the amount of outstanding work done by Canadian researchers. A bilingual Web site, a web-based specialist's discussion program and bilingual pamphlets facilitate public awareness and allow patients to voice concerns.